Cellular senescence enhances adaptive anticancer immunosurveillance - Ines Marin; Manuel Serrano; Federico Pietrocola (OncoImmunology, 2023)
Cancer therapy often induces senescence in some cancer cells. Senescent cells, due to their profoundly altered biology, may conceivably interact with the adaptive immune system in novel ways that may boost cancer immunosurveillance, triggering the clearance of both senescent and non-senescent neoplastic cells. In this regard, we have recently reported that senescent cancer cells exhibit potent antigenicity and adjuvanticity and can elicit strong CD8+ T cell-dependent anticancer effects when used as vaccination agents.